Comparison Between the Forensic Medicine Departments and the Unit of Council of Forensic Medicine in Kocaeli in Related with Forensic Service - Çolak, Başar; Biçer, Ümit; Doğan, Türker; Kurtaş, Ömer; Gündoğmuş, Ümit Naci; Demirbaş, İlkgül (The Bulletin of Legal Medicine, 2003)
Although Council of Forensic Medicine (CFM) and Forensic Medicine Departments of University are both defined as official expertise centers for medicolegal cases, forensic expertise services are carried out by Units of Council of Forensic Medicine in practice. Under ordinary circumstances , forensic medicine departments should take responsibility not only for education but also science and technology improvement. Insufficient contribution of forensic medicine departments to the forensic expertice service is an handicap to spread the service and make it faster. We compare the statistical data of forensic services for the years 1998-2002 that was held by two different forensic expertise office. We found that most of the forensic reports were prepared by the Units of CFM, (98.1% of all reports) while only a small proportion of the reports were prepared by the Forensic Medicine Departments, Kocaeli University, Faculty of Medicine (1.9%).The proportion of reports about other aspects of forensic subjects between two offices are as follows; 96.3% of the reports of sexual assaults were prepared by the units of CFM, while only 3.7 % of them was prepared by the forensic medicine departments. 97.6% of the reports related with forensic psychiatry was prepared by the units of CFM, and 2.4% of them were prepared by the forensic medicine departments. We found that post mortems were carried out only by the forensic specialists from the units of CFM. As a conclusion, appropriate contribution of the forensic medicine departments in the forensic field can decrease excessive work load on the units of CFM, reducing the need for general practitioners and would be beneficial for educational duty of forensic medicine departments. Keywords: The Council of Forensic Medicine, The Forensic Medicine Department, Forensic Specialist, Autopsy, Corpse Evaluation, Sexual Assault, Forensic Psychiatry